Brain Structural and Functional Alterations Specific to Low Sleep Efficiency in Major Depressive Disorder - Yang, Ying; Zhu, Dao-min; Zhang, Cun; Zhang, Yu; Wang, Chunli; Zhang, Biao; Zhao, Wenming; Zhu, Jiajia; Yu, Yongqiang (Frontiers in Neuroscience, 2020)
Background: Sleep disturbance is common in patients with major depressive disorder (MDD), but the exploration of its neural underpinnings is limited by subjective sleep measurement and single-modality neuroimaging analyses. Methods: 96 patients with MDD underwent polysomnography examinations and multi-modal magnetic resonance imaging (MRI) scans. According to sleep efficiency, patients were subdivided into well-matched normal sleep efficiency (NSE, N = 42; 14 men; aged 43 ± 10 years) and low sleep efficiency (LSE, N = 54; 23 men; aged 45 ± 12 years) groups. Inter-group differences in brain structure and function were examined by applying voxel-based morphometry, regional homogeneity (ReHo) and functional connectivity strength (FCS), and tract-based spatial statistics approaches to structural, functional, and diffusion MRI data, respectively. Results: There was no significant difference in gray matter volume between the NSE and LSE groups. Compared with the NSE group, the LSE group showed increased axial diffusivity in the left superior and posterior corona radiata, and left posterior limb and retrolenticular part of internal capsule. In addition, the LSE group exhibited decreased ReHo in the bilateral lingual gyri and right postcentral gyrus yet increased FCS in the left angular gyrus relative to the NSE group. Moreover, validation analyses revealed that these results remained after adjusting for the medication effect. Conclusion: Our data indicate that preserved gray matter morphology, impaired white matter integrity, and decreased local synchronization degree yet increased functional connectivity strength are specific to low SE in MDD patients. These findings of disassociation between structural and functional alterations might provide insights into the neural mechanisms of sleep disturbance in depression.